2015
DOI: 10.1160/th14-12-1075
|View full text |Cite
|
Sign up to set email alerts
|

Atheroprotective role of C5ar2 deficiency in apolipoprotein E-deficient mice

Abstract: Atherogenic processes and vascular remodelling after arterial injury are controlled and driven by a plethora of factors amongst which the activation of the complement system is pivotal. Recently, we reported a clear correlation between high expressions of the second receptor for complement anaphylatoxin C5a, the C5a receptor-like 2 (C5L2, C5aR2), with high pro-inflammatory cytokine expression in advanced human atherosclerotic plaques. This prompted us to speculate that C5aR2 might have a functional role in ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…C5aR2 was absent in CD3 + T cells and vascular smooth muscle cells. This proatherogenic role of C5aR2 and its collaboration with C5aR1 were confirmed in vivo mouse models of wire-induced endothelial injury and high-fat diet-induced atherosclerosis [66]. Here, C5aR2 levels were elevated in aortas of wire-injured mice or mice on high-fat diet (12 weeks), both of atherosclerosis-prone ApoE KO.…”
Section: Controversial Issue Four: Is C5ar2 a Pro- Or Anti-inflammsupporting
confidence: 56%
See 2 more Smart Citations
“…C5aR2 was absent in CD3 + T cells and vascular smooth muscle cells. This proatherogenic role of C5aR2 and its collaboration with C5aR1 were confirmed in vivo mouse models of wire-induced endothelial injury and high-fat diet-induced atherosclerosis [66]. Here, C5aR2 levels were elevated in aortas of wire-injured mice or mice on high-fat diet (12 weeks), both of atherosclerosis-prone ApoE KO.…”
Section: Controversial Issue Four: Is C5ar2 a Pro- Or Anti-inflammsupporting
confidence: 56%
“…But on neutrophils from bone marrow of C5aR2 KO mice, the surface expression of C5aR1 is lower than on those from WT mice [68]. Surface C5aR1 expression on nonstimulated BMDMs from C5aR2 KO mice is lower compared with those from WT littermates, also observed for C5aR2/ApoE double KO [66]. C3aR expression levels in neutrophils were similar between C5aR2 KO and WT mice [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests involvement of possible C5aR2–TLR4 crosstalk in the induction of HMGB1 that appears to require mitogen‐activated protein MEK1/2, JNK1/2, and PI3K . Moreover, C5aR2 was shown to mediate C5a‐induced activation of mast cells and to promote atherosclerosis and neointimal plaque formation in apolipoprotein E‐deficient mice . In contrast to these pro‐inflammatory roles by C5aR2, other studies showed that C5aR2 interacts physically with and negatively regulates C5aR1 signaling in neutrophils and macrophages, thereby providing a mechanistic basis for its reported anti‐inflammatory action .…”
Section: Regulation Of Immune and Inflammatory Responses By Complemenmentioning
confidence: 95%
“…The underlying signaling mechanism involves induction of PI3K or ERK1/2 signaling, which in turn suppress crucial transcription factors (IRF-1 and IRF-8) that regulate these cytokines mediate C5a-induced activation of mast cells 41 and to promote atherosclerosis and neointimal plaque formation in apolipoprotein E-deficient mice. 42 In contrast to these pro-inflammatory roles by C5aR2, other studies showed that C5aR2 interacts physically with and negatively regulates C5aR1 signaling in neutrophils and macrophages, 39,43 thereby providing a mechanistic basis for its reported anti-inflammatory action. 36 In toto, the activities of C5aR2 appear to be dynamic and contextual depending on cell type, tissue, and disease model.…”
Section: Regulation Of Immune and Inflammatory Responses By Complemmentioning
confidence: 99%